Nilai-Nilai Pendidikan Islam dalam Tradisi Janengan serta Relevansinya dengan Karakter Nabi Muhammad - Abdi Azizurahman; Sedya Santosa (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2022)
This research is motivated by a cultural reality produced by the life of the Javanese people, especially the Janengan tradition. The Janengan tradition is a Javanese-Islamic traditional musical art by reading the Prophet's prayers in Javanese style. This tradition has grown and developed in North Pontianak. Unfortunately, the people in North Pontianak interpret this tradition as the art of traditional music without knowing the goals and values ​​conveyed directly or explicitly. This research is part of the relevance of the character of the Prophet Muhammad to the Janengan tradition in FAST theory (Fatanah, Amanah, Siddiq, Tablig). This research aims to explore the values ​​of Islamic education in the Janengan tradition, both in terms of implementation and reading texts of the Janengan tradition and their relevance to FAST theory. This research method uses qualitative research with the type of descriptive research. They were collecting data using observation, interview, and documentation techniques. The implementation of the Janengan tradition begins with the opening of the reading of Al-Fatihah, reading the Janengan poetry, and prayer. The five musical instruments used show the five mandatory prayers. The way of sitting in its implementation shows equality in the eyes of Allah SWT; the value of monotheism, the value of worship, and moral values ​​are collected in prayer activities. The poems that are read also have messages and values ​​, namely the value of monotheism, the value of worship, and the value of morals. The Janengan tradition contains the four obligatory nature of the prophets; intelligence-can be trusted-honesty-convey, FAST.